THU0175 REAL-WORLD EXPERIENCE OF SWITCHING FROM ORIGINATOR TO BIOSIMILAR RITUXIMAB IN RHEUMATOID ARTHRITIS. (2nd June 2020) - Melville, A.; MD Yusof, M. Y.; Fitton, J.; Bailey, L.; Emery, P.; Buch, M. H.; Dass, S.; Saleem, B.
Abstract : Background: Pre-clinical and trial data confirm biosimilar rituximab (RTX-B) has equivalent physicochemical properties, function, efficacy and safety as originator (RTX-O) 1, 2 . However, real-world data are lacking, including non-medical switch to RTX-B in patients established on RTX-O. Loss of response (LOR) has been observed following open-label switch to other biosimilars 3, and it is unclear how patients who develop LOR after switching should be managed. Objectives: To describe our real-world experience of non-medical switch from RTX-O to RTX-B in RA and explore treatment strategies for patients developing LOR to RTX-B (switch back to RTX-O versus other b/tsDMARDs). Methods: We conducted a retrospective observational study of RTX-treated RA patients in Leeds from May 2002–Jan 2020. From Oct 2017, all patients on RTX-O were switched to RTX-B unless specified by treating clinician or informed consent not obtained. Demographic and clinical data were collected from electronic health records. Effectiveness was assessed by DAS28-CRP and RTX retention (using Kaplan-Meier method). Changes in treatment were based on clinician judgment. Results: 944 patients with RA received ≥1 cycle of RTX in Leeds over the past 17 years. Of these, 358 required RTX re-treatment during the study period (Oct 2017–Jan 2020); 263 (73.5%) switched to RTX-B, whilst 95 (26.5%) remained on RTX-O (medical reason=46.3%; patient decision=53.7%). 256/263 patients on RTX-B with 4-month data were analysed. 201/256 (78.5%) were female, mean (SD) age 63.1 (12.4), 97.7% seropositive, 81.6% on csDMARD (62.9% methotrexate), 14.8% oral steroid, 58.6% had previous bDMARDs, and mean (SD) RTX-O cycles pre-switch was 6 (3.6). Total follow-up was 378 patient-years. Mean (SD) DAS28-CRP was 3.01 (1.17) 4 months post-last cycle RTX-O and 3.32 (1.31) post-switch to RTX-B (mean diff +0.30, 95% CI 0.004-0.60; p=0.047), with increase in VAS (+5.7, 95% CI 0.09-11.37; p=0.047), but not SJC, TJC or CRP. At last follow-up, 185/256 (72.3%) patients remained on RTX-B [median (range) RTX-B cycles 2 (1-4)]. RTX-B retention rate estimates were 79.4% and 71.3% at 12 and 18 months respectively. Following RTX-B discontinuation, 33/256 patients (12.8%) switched back to RTX-O [LOR=30 (11.7%), adverse effects (AEs)=3 (1.2%)], 13/256 (5.1%) started other b/tsDMARDs, and 25/256 (9.7%) stopped treatment (no longer indicated=7, deaths=7, loss to follow-up=6, patient choice=3, new contraindication=2). Of 46 patients with LOR/AE to RTX-B, 39 discontinued after cycle 1 (C1), 5 after C2 and 2 after C3. 31/33 patients switched back to RTX-O remained on treatment but follow-up was limited [mean (SD) 7.5 (5.2) months; 23/33 had 1 cycle only]. Compared with patients treated with other b/tsDMARDs, those switched back to RTX-O had more previous RTX-O cycles [mean (SD) 6.67 (3.28) versus 2.62 (2.10); p<0.0001]. Compared with patients who remained on RTX-B (n=185), those who discontinued for LOR/AE/death (n=53) had more previous bDMARDs (mean 1.26 vs 0.83; difference 0.43, 95% CI 0.10-0.77, p=0.01), but no differences in other clinical characteristics, treatment or B-cell numbers. Conclusion: Our real-world single-centre experience of non-medical switch from RTX-O to RTX-B in RA showed approx. three quarters of patients remained on RTX-B and maintained stable disease activity. However, apparent LOR occurred in 16%. Of >10% switched back to RTX-O, the majority remained on treatment at short-term follow-up. References: [1]Lee at al, MAbs 2018. [2]Shim et al, Rheumatology 2019. [3]Tweehuysen et al, AR 2018. Disclosure of Interests: Andrew Melville: None declared, Md Yuzaiful Md Yusof: None declared, John Fitton Speakers bureau: Pfizer, Lynda Bailey Speakers bureau: Chugai, Sanofi, Paul Emery Grant/research support from: AbbVie, Bristol-Myers Squibb, Merck Sharp & Dohme, Pfizer, Roche (all paid to employer), Consultant of: AbbVie (consultant, clinical trials, advisor), Bristol-Myers Squibb (consultant, clinical trials, advisor), Lilly (clinical trials, advisor), Merck Sharp & Dohme (consultant, clinical trials, advisor), Novartis (consultant, clinical trials, advisor), Pfizer (consultant, clinical trials, advisor), Roche (consultant, clinical trials, advisor), Samsung (clinical trials, advisor), Sandoz (clinical trials, advisor), UCB (consultant, clinical trials, advisor), Maya H Buch Grant/research support from: Pfizer, Roche, and UCB, Consultant of: Pfizer; AbbVie; Eli Lilly; Gilead Sciences, Inc.; Merck-Serono; Sandoz; and Sanofi, Shouvik Dass Consultant of: Roche, Speakers bureau: Roche, Benazir Saleem Speakers bureau: Sanofi